2013
DOI: 10.3851/imp2652
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Tenofovir-Based Regimens during Treatment Failure of Subtype C HIV-1 in South Africa

Abstract: Background Tenofovir disoproxil fumarate (TDF) is increasingly available for patients infected with subtype C HIV-1. This subtype is reported to develop the principle TDF resistance mutation in the HIV reverse transcriptase, K65R, with greater propensity than other subtypes. We sought to describe K65R development during TDF use in a cohort of patients infected with subtype C HIV. Methods Using a prospectively followed cohort with 6 monthly HIV RNA assays, we identified virologic failure (defined as an HIV RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The high overall (89%) and dual-class (83%) resistance is consistent with other reports from AMPATH [23,26] and other RLS upon any (not solely TDF-based) first-line ART [37]. The few studies that evaluated resistance in TDF-based first-line regimens in RLS, mostly in subtypes C, G and CRF02_AG from Southern Africa and Nigeria, do not report overall resistance but estimate NRTI- (94 to 100%) and NNRTI-associated resistance (57 to 97%) to be high [911,13,16]. Though mutation frequencies in this study, other than K65R, were similar to prior reports [13], unique mutation patterns in 58% of the patients and specific mutation co-occurrence support the need for continued research on subtype-specific resistance, particularly with changing treatment guidelines [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high overall (89%) and dual-class (83%) resistance is consistent with other reports from AMPATH [23,26] and other RLS upon any (not solely TDF-based) first-line ART [37]. The few studies that evaluated resistance in TDF-based first-line regimens in RLS, mostly in subtypes C, G and CRF02_AG from Southern Africa and Nigeria, do not report overall resistance but estimate NRTI- (94 to 100%) and NNRTI-associated resistance (57 to 97%) to be high [911,13,16]. Though mutation frequencies in this study, other than K65R, were similar to prior reports [13], unique mutation patterns in 58% of the patients and specific mutation co-occurrence support the need for continued research on subtype-specific resistance, particularly with changing treatment guidelines [38].…”
Section: Discussionmentioning
confidence: 99%
“…K65R is a TDF signature mutation conferring resistance to all NRTIs but AZT, is rarely transmitted [27], is less common in subtype B-infected patients failing therapy [15], and is variable in RLS [911,13,16]. The high barrier to K65R development as reported in resource-rich settings may reflect high potency of K65R-selecting drugs, significant viral fitness constraints and unique RNA structural considerations [20].…”
Section: Discussionmentioning
confidence: 99%
“…In patients on tenofovir-based regimens, almost 30% failed with K65R and half with M184V (36). In South African patients failing first line ART with TDF/FTC, K65R was detected in 5 of 40 (12%) and M184V/I in 12 of 40 (28%) (37). Another South African study looking at 80 patients failing on TDF-based ART with at least one resistance mutation found 10 (12.5%) had K70E, 43 (54%) had K65R and 72 (90%) had M184I/V (38*).…”
Section: Transmitted Resistance and Resistance In Individuals Failingmentioning
confidence: 99%
“…This study concluded that TAF may be beneficial for individuals harboring certain resistant viruses [47]. The K65R mutation is a 'hallmark' resistance mutation of TFV and is associated with virologic failure in individuals administered TDF [48]. The utility of TFV prodrugs may be extnded if they are coadministered with an NAI with 'resistance repellant' properties versus K65R such as zidovudine (ZDV).…”
Section: Highlighted Nucleoside Antiviral Prodrugsmentioning
confidence: 99%